Datacollection in Event-Driven Wireless Sensor Networks with Mobile Sinks. (26th July 2010) - Sabbineni, Harshavardhan; Chakrabarty, Krishnendu
Abstract : We present a two-tier distributed hash table-based scheme for data-collection in event-driven wireless sensor networks. The proposed method leverages mobile sinks to significantly extend the lifetime of the sensor network. We propose localized algorithms using a distributed geographic hash-table mechanism that adds load balancing capabilities to the data-collection process. We address the hotspot problem by rehashing the locations of the mobile sinks periodically. The proposed mobility model moves the sink node only upon the occurrence of an event according to the evolution of current events, so as to minimize the energy consumption incurred by the multihop transmission of the event-data. Data is collected via single-hop routing between the sensor node and the mobile sink. Simulation results demonstrate significant gains in energy savings, while keeping the latency and the communication overhead at low levels for a variety of parameter values.